Understanding The Role of Local Culture and Local Food in Indonesia’s Gastronomy Tourism - Sandy Dwiputra Yubianto (Jurnal Hospitality dan Pariwisata, 2023)
Indonesia is an archipelagic country that has a diverse culture. Each island has its own history that has made their distinctive social norms and local beliefs grow stronger. As Indonesia is also a multicultural country, each part of the nation has its own specialty in its cuisine, way of living, habits, and thus created unique traditions through its culture. This factor has brought up the attention of the researcher to actually examine how the previous study in Indonesia’s culture has many relations towards the food itself mainly focusing on the appearance of the food, and the local’s culture to see how indigenous they are to expose the value of gastronomy as a concept of tourism. These 2 factors of local culture and local food seems to have brought Indonesia to a new exposure for its gastronomy Tourism worldwide. Not many countries have an exponential range of food types, with its many intriguing uses of ingredients that seems inviting for some people, who crave to explore for their belly, as well as to dive into the service experience in that particular destination. The study uses Literature review to examine how the past studies have revealed some of the important factors of local culture and local food in supporting the exposure of Indonesia's Gastronomy tourism. The descriptive analysis is used to explain more on the role of these 2 factors in enhancing gastronomy tourism. The result of these study shows that local culture and local food both act simultaneously giving a big role in influencing people to actually visit some destinations in Indonesia. The fascination of the people, the tradition and their cuisine that helped by the looks and the availability of surrounding raw materials has driven attention towards its own market and helped destination bring its own brand of Gastronomy tourism.